2022
DOI: 10.5851/kosfa.2021.e61
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flutriafol Exposure on Residue Characteristics in Pig Muscle and Fat Tissue

Abstract: This study investigated the effect of exposure to flutriafol based on residues in pigs. Pigs were exposed to different concentrations (0.313, 0.625, 3.125, 6.25, and 12.5 mg/kg bw/d, n=20) for 4 wk in different treatment groups. Serum biochemical analysis, residue levels, and histological analysis were conducted using the VetTest chemistry analyzer, liquid chromatography mass spectrometry, and Masson’s trichrome staining, respectively. The body weight (initial and final) was not significantly different between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…Thus, tebuconazole treatment at different concentrations for 28 d did not affect the growth performance of pigs. These results are similar to those of other previous studies ( Jeong et al, 2021 ; Jeong et al, 2022 ; Lopez-Antia et al, 2021 ). Propiconazole and flutriafol were not significantly different between control and the treatment groups in pigs and chicks.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Thus, tebuconazole treatment at different concentrations for 28 d did not affect the growth performance of pigs. These results are similar to those of other previous studies ( Jeong et al, 2021 ; Jeong et al, 2022 ; Lopez-Antia et al, 2021 ). Propiconazole and flutriafol were not significantly different between control and the treatment groups in pigs and chicks.…”
Section: Resultssupporting
confidence: 93%
“…ALT regulates transamination and is a marker for functional damage in the liver and kidney ( Firat et al, 2011 ; Ochiai et al, 2020 ; Sookoian and Pirola, 2012 ). Previous studies have also shown that triazole fungicides (i.e., propiconazole and flutriafol) increased the ALT levels in pigs ( Jeong et al, 2021 ; Jeong et al, 2022 ). ALT levels increase ROS levels and oxidative damage ( Patil et al, 2009 ; Singh et al, 2011 ).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations